Efforts to Encourage Sustainable Performance of Corruption Eradication Commission Employees Through Training Programmes - Koto, Mita; Zainal, Veithzal Rivai; Hakim, Azis (PANDITA: Interdisciplinary Journal of Public Affairs, 2025)
This study aims to determine and analyse the efforts made by the Corruption Eradication Commission to support the sustainable performance of its employees through employee development programs that are in accordance with job competency standards and career development plans. This research was conducted using a descriptive qualitative approach. Primary data sources were obtained from research results in the form of manuscripts, field notes, memos, and other supporting documents. The results of the research show that although the Corruption Eradication Commission has only been a state institution in the executive power family under the president for approximately 3 (three) years and the Corruption Eradication Commission employees have changed their status to become state civil apparatus (ASN), the Corruption Eradication Commission has been able to adjust its human resource development policies implemented through formal learning programmes such as formal training and education and through non-formal learning in accordance with statutory provisions governing competency development for State Civil Apparatus which include technical competence, functional competence, managerial competence, and socio-cultural competence. It is expected that the competency development policy at the Corruption Eradication Commission is not only aimed at increasing professionalism but also maintaining and improving the integrity of its human resources which is the hallmark of the institution.